Produção de queijo de minas artesanal na região serras da Ibitipoca: reconhecimento legítimo e estratégico para fortalecimento dos agricultores familiares - Pereira, Maria Dalva (2018)
The appreciation of traditional products can represent a sustainable rural development strategy, which is a necessity of the “Serras da Ibitipoca” region. Therefore, it is required that the organization of farmers and the local production regularize such products. From this perspective, the aim of this work was to contribute with the recognition of the “Serras da Ibitipoca” region as a producer of Minas Artisanal Cheese - MAC. In order to support this work, we first discuss the concept of family farming and its importance, traditional agri-food products and cheese production in Brazil. In order to carry out the research, which sought to identify the existing elements in the region that could justify its recognition, partnerships were signed, with which we worked in a participatory manner. Initially, we aimed at identifying and articulating the interest group for the recognition of MAC production in the region, which is a fundamental factor for the development of the research. The research was characterized as qualitative. The objectives are exploratory; the procedures of the research are action based; and the basis is theoretical and practical. Data collection was done through bibliographic studies, three interviews, 50 questionnaires, meetings, observation, as well as documents and public statistical data. As sample, 12 towns that belong to the “Serras da Ibitipoca” region were surveyed. This study includes the research on the process of recognition of a region as producer of MAC, historical survey of the production of MAC in the region and characterization of the region economic, social and physical aspects. As identified in the research, the “Serras da Ibitipoca” region has a history of cheese production dating back to the thirteenth century, a place where there was dairy activity and that was inclined to the production of cheeses. Something that is fundamental for this process of recognition is an interest group formed by producers, representatives of the towns and family farmers, research, inspection and extension agencies. The existence of the mentioned elements justifies the recognition of the region as producer of MAC. Other elements such as maintenance of the activity in the informality despite the repression of the inspection, consumer food security, generation of better income to the producers and possibility of this activity to boost tourism in the region, strengthen this justification. Therefore, we conclude that the “Serras da Ibitipoca” region has the potential to gain recognition as a producer of MAC. From this conclusion, and using the results of this research, we construct, in a participative way, the document "Characterization of the “Serras da Ibitipoca” region ", which is a requirement to request the recognition of the region as producer of MAC within the Instituto Mineiro de Agropecuária IMA.